Co-Immunoprecipitation Reveals Interactions Between Amelogenin and Ameloblastin via Their Self-Assembly Domains - Bapat, Rucha Arun; Su, Jingtan; Moradian-Oldak, Janet (Frontiers in Physiology, 2020)
Macromolecular assembly of enamel extracellular matrix proteins (EMPs) is intimately associated with the nucleation, growth and maturation of highly organized hydroxyapatite crystals giving rise to healthy dental enamel. Although the colocalization of two of the most abundant EMPs amelogenin (Amel) and ameloblastin (Ambn) in molar enamel has been established the evidence towards their interaction is scarce. We used co-immunoprecipitation (co-PI) to show evidence of direct molecular interactions between recombinant and native Amel and Ambn. Ambn fragments containing Y/F-x-x-Y/L/F-x-Y/F self-assembly motif were isolated from the co-IP column and characterized by mass spectroscopy. We used recombinant Ambn mutants with deletion of exons 5 and 6 as well as Ambn derived synthetic peptides to demonstrate that Ambn binds to Amel via its previously identified Y/F-x-x-Y/L/F-x-Y/F self-assembly motif at the N-terminus of its exon 5 encoded region. Using an N-terminal specific anti-Ambn antibody, we showed that Ambn N-terminal fragments colocalized with Amel from secretory to maturation stages of enamel formation in a single section of developing mouse incisor, and closely followed mineral patterns in enamel rod interrod architecture. We conclude that Ambn self-assembly motif is involved in its interaction with Amel in solution and that colocalization between the two proteins persists from secretory to maturation stages amelogenesis. Our in vitro and in situ data support the notion that Amel and Ambn may form heteromolecular assemblies that may perform important physiological roles during enamel formation.